Wetlands construídos como pós-tratamento de decanto-digestor seguido de filtro anaeróbio - Reis, Wilhan Douglas dos (2018)
With a growing population demand in Higher Education Institutions (HEIs), the quantity of wastewater is increased, when it is released without treatment or with inefficient treatment, it contributes significantly to the pollution of water resources. In this context, the objective of this work is to evaluate the performance of Wetlands Constructed (WC) as post-treatment of decant-digester followed by anaerobic filter, operated with effluent from the Federal University of Mato Grosso Campus Cuiabá-MT, removal of nutrients and organic matter. For the development of the research, four Wetlands were constructed: WCT - planted with Thypha domingensis, WCH - planted with Heliconia psittacorum, WCP planted with Pontederia Parviflora, and WCB - not planted. Total Solids (ST), Total Dissolved Solids (TDS), Biochemical Oxygen Demand (BOD5), Chemical Oxygen Demand (COD), total nitrogen, phosphorus, sulfate, nitrate and nitrite. The results show an organic matter removal experiment with average removal results: 70% BOD5 for WCT, WCH and WCP; and COD 76% for WCP. The mean removal of total phosphorus was 78% for WCP and 92% NO-2 , as macronutrients. An analysis of variance ANOVA showed significance in the results of STD, SO4 and COD removal.